2016
DOI: 10.1016/j.yhbeh.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gestational stress and Selective Serotonin reuptake inhibitor antidepressant treatment on structural plasticity in the postpartum brain — A translational model for postpartum depression

Abstract: Postpartum depression (PPD) is a common complication following childbirth experienced by one in every five new mothers. Although the neural basis of PPD remains unknown previous research in rats has shown that gestational stress, a risk factor for PPD, induces depressive-like behavior during the postpartum period. Moreover, the effect of gestational stress on postpartum mood is accompanied by structural modifications within the nucleus accumbens (NAc) and the medial prefrontal cortex (mPFC) – limbic regions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 73 publications
4
33
0
3
Order By: Relevance
“…UHPLC–MS/MS analysis showed that the 5-HT concentration in the prefrontal cortex in the T group, which showed depressive behavior, was significantly lower than that in the C group ( p < 0.05; Figure 5 ). These findings support the hypothesis that prefrontal cortex BDNF and 5-HT are involved in PPD (Suda et al, 2008; Haim et al, 2016). …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…UHPLC–MS/MS analysis showed that the 5-HT concentration in the prefrontal cortex in the T group, which showed depressive behavior, was significantly lower than that in the C group ( p < 0.05; Figure 5 ). These findings support the hypothesis that prefrontal cortex BDNF and 5-HT are involved in PPD (Suda et al, 2008; Haim et al, 2016). …”
Section: Resultssupporting
confidence: 88%
“…The prefrontal cortex is a brain region which has been linked to cognitive behavior, personality expression, and social behavior, including PPD (Moses-Kolko et al, 2010; Haim et al, 2016; Palmfeldt et al, 2016), and is important in the development and treatment of depression (Koenigs and Grafman, 2009). Local thyroid hormone deficiency was noted prior to the reduction in plasma and was found to be related to depressive behaviors (Ge et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Humán felmérések (Moses-Kolko et al, 2014) és rágcsálókon végzett kísérletek (Gemmel et al, 2016;Haim et al, 2016;Pawluski et al, 2016) is bizonyítják azt a tényt, hogy a stressznek idegrendszert befolyásoló hatása van a terhesség alatti időszakban, ugyanis a terhesség alatti folyamatos stressz szorongásos viselkedést és a szülői gondoskodás hiányát eredményezte a terhesség után (Darnaudéry et al, 2004;Smith et al, 2004;Brummelte & Galea, 2010). Ez a megfigyelés a depresszió szinaptogenikus hipotézisével összhangban állhat (Hajszan et al, 2010), miszerint a terhesség alatti stressz az idegsejtek specifikus strukturális változását válthatja ki az anya központi idegrendszerében, hozzájárulva a szülést követő megváltozott kedélyállapothoz .…”
Section: A Terhesség Utáni (Posztpartum) Depresszióunclassified
“…Számos, rágcsálókon végzett tanulmány számol be arról, hogy a terhesség alatti tartós stressz a szülést követően szorongásos viselkedést és a szülői gondoskodásban való deficitet okoz (Darnaudéry et al, 2004;Smith et al, 2004;O'Mahony et al, 2006;Brummelte & Galea, 2010;Hillerer et al, 2011). Humán vizsgálatokkal bizonyították, hogy a terhesség alatti időszakban az erős stressz befolyásolja a hippokampális neurogenezist és a CA3 piramissejtek dendritikus morfológiáját , továbbá csökkenti a prefrontális kéregben és a bazális előagyi nucleus accumbens héj régiójában lévő principális sejtek dendrittüskéinek számát és a dendritarborizációjuk sűrűségét (Leuner et al, 2014;Haim et al, 2016), míg növeli a gyrus cinguli kérgi régióban a szinaptofizin szintjét és a bazolaterális amigdalában a dendrittüskék számát (Gemmel et al, 2016;Haim et al, 2016). E változások egy részét antidepresszáns-kezelésekkel vissza lehetett fordítani (Gemmel et al, 2016;Haim et al, 2016).…”
Section: A Stressz Hatása Az Anyai Idegrendszerreunclassified
See 1 more Smart Citation